Welfare Benefit Reforms and Employment - Marta Aloi; Teresa Lloyd-Braga; Manuel Leite-Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2017)
We consider an economy characterised by involuntary unemployment among low skilled workers, and investigate the implications for employment and income of welfare schemes often advocated as less distortionary. We show that reducing unemployment benefits in favour of income subsidies (social benefits) reduces employment in general equilibrium and also the income of low skilled workers, for not too high distortions in the labour market. Furthermore, it leads to a higher tax burden and a welfare deterioration. To support employment, we suggest that systems grounded in contribution-based unemployment insurance schemes are to be preferred and strengthened.
Keywords: H20; I38; J65; 330; unemployment benefits; social benefits; taxes; unions; employment